ÂNIMA: An Introduction to Puppet Theater With Online Lessons (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This text is a student’s experience report in the training course “Anima: An Introduction to Puppet Theatre” held between October and November 2020 via online classes. The training process for an actor/animator, i.e. the person who brings the idea of anima (or life) to an inanimate object, can be imbued with nuances that vary from the possibilities of making the puppet to the techniques used to give it anima. This report's goal will be to reflect on the Puppet Theatre training process held via online classes. Each student needs a computer, cellphone, or tablet to watch the lessons at home, synchronously, in real-time, and participate in the practical and theoretical activities. The course was developed on the ZOOM platform on Mondays and Wednesdays, from 6p.m. to 8p.m. (Brasília Time). People from different states in Brazil, and also from abroad, took part as students. As a final result, a scenic exercise was presented to the guests on the ZOOM platform.
Keywords: Online classes/ synchronous; Puppet Theater; Theater Pedagogy; Formation of actor/animator